Release film

JP7936763B2Active Publication Date: 2026-10-16OJI HLDG CORP
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2023053152
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2023-03-29
Publication Date
2026-10-16
Estimated Expiration
2038-05-31

AI Technical Summary

Benefits of technology

【0011】 本発明によれば、基材層上に表面層を有する剥離性フィルムであって、剥離性フィルムの成分が物品に移行し難く、加熱前後の剥離力の差が小さい剥離性フィルムを提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007936763000001
    Figure 0007936763000001
  • Figure 0007936763000002
    Figure 0007936763000002
  • Figure 0007936763000003
    Figure 0007936763000003
Patent Text Reader

Abstract

To provide a releasable film having a surface layer on a substrate layer in which a component of the releasable film hardly migrates into an object and the release power before and after heating is small.SOLUTION: There is provided a releasable film having a surface layer on a substrate layer, in which the main component forming the surface layer is a resin component, the resin component comprises a modified acrylic resin (A) having an alkyl component and a crosslinkable functional group, a resin (B) different from the modified acrylic resin (A) and a cross-linking agent (D), the modified acrylic resin (A) contains at least a structural unit represented by the following general formula (I): (R1 represents a methyl group or a hydrogen atom; and R2 represents an alkyl group having 10 to 18 carbon atoms) and the cross-linking agent (D) is a melamine compound having a structure in which all hydrogen atoms of an amino group are substituted with at least one of an alkoxy alkyl group and an alkanol group.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] The present invention relates to a release film and a method for producing the same. [Background technology]

[0002] Release films are used in industrial fields such as the manufacturing processes of electronic components and electronic circuit boards, and thermosetting resin components such as fiber-reinforced plastics, as well as in the medical field, such as for adhesive patches and bandages.

[0003] Such release films are known to be used in a variety of applications, such as surface protection films and adhesive tapes, release liners and separator films, separators used in semiconductor manufacturing processes (dicing, die bonding, backgrinding, etc.), carriers for forming unfired sheets in ceramic capacitor manufacturing, carriers in composite material manufacturing, and separator films for protective materials.

[0004] For example, silicone-based release films have excellent weather resistance, heat resistance, cold resistance, chemical resistance, and electrical insulation properties, and are widely used as release films. However, when using silicone-based release films, silicone may transfer (migrate) to the article to which the film is applied (this problem is also called the silicone migration problem). Therefore, efforts have been made to improve the composition of silicone in silicone-based release films, minimize the amount of silicone used, or avoid using silicone altogether. For example, Patent Document 1 proposes a release film using a hydroxyl group-containing long-chain alkyl polymer. [Prior art documents] [Patent Documents]

[0005] [Patent Document 1] Japanese Patent Publication No. 2015-030795 [Overview of the Initiative] [Problems that the invention aims to solve]

[0006] However, the release film described in Patent Document 1 has insufficient heat resistance due to the large difference in release force before and after heating. As an example, let's consider the case where the release film is used as a carrier for forming an unfired sheet during the manufacture of ceramic capacitors. In order to produce the unfired sheet, a coating layer is applied to the release film and dried. If the heat resistance is insufficient due to the large difference in release force before and after heating, the unfired sheet will become difficult to peel off from the release film unexpectedly due to the heat of drying after the drying process. Depending on the release film, the unfired sheet may not only become difficult to peel off from the release film unexpectedly, but may even peel off unexpectedly. Because of these problems, it is difficult to use the release film as a substitute film for silicone-based release films.

[0007] Furthermore, similar to the silicone migration problem caused by silicone-based release films, there is a problem where components of the release film migrate to the surface of an article, and if these components remain on the article's surface after the release film is removed, the article's surface becomes contaminated. Residual components on the article's surface not only contaminate the article itself, but also lead to contamination of the surfaces of other articles that subsequently come into contact with it. Therefore, release films used in the manufacturing processes of precision equipment such as electronic components and electronic circuit boards are required to have properties that make it difficult for components of the release film to migrate to the article.

[0008] Under these circumstances, the main objective of the present invention is to provide a release film in which the components of the release film are less likely to transfer to the article and in which the difference in release strength before and after heating is small. [Means for solving the problem]

[0009] The present inventors have conducted intensive studies to solve the aforementioned problems. As a result, in a peelable film having a surface layer on a base material layer, the main component forming the surface layer is a resin component, and the resin component includes a modified acrylic resin (A) having an alkyl component and a crosslinkable functional group, a resin (B) different from the modified acrylic resin (A), and a crosslinking agent (D), and the modified acrylic resin (A) has at least the following general formula (I):

Chemical Formula

[0010] That is, the present invention includes the following matters. [1] A peelable film having a surface layer on a base material layer, wherein the main component forming the surface layer is a resin component, the resin component includes a modified acrylic resin (A) having an alkyl component and a crosslinkable functional group, a resin (B) different from the modified acrylic resin (A), and a crosslinking agent (D), the modified acrylic resin (A) has at least the following general formula (I):

Chemical Formula

Chemical Formula

Effects of the Invention

[0011] According to the present invention, it is possible to provide a release film having a surface layer on a base material layer, in which components of the release film are less likely to transfer to an article, and the difference in peel force before and after heating is small.

Modes for Carrying Out the Invention

[0012] The release film according to the present embodiment is a release film having a surface layer on a base material layer, wherein the main component forming the surface layer is a resin component, and the resin component comprises a modified acrylic resin (A) having an alkyl component and a crosslinkable functional group, a resin (B) different from the modified acrylic resin (A), and a crosslinking agent (D), and the modified acrylic resin (A) has at least the following general formula (I):

Chemical Formula

[0013] The release film according to this embodiment exhibits the characteristics that, due to its configuration, the components of the release film are less likely to migrate to the article and that there is a small difference in release force before and after heating. More specifically, (1) when an object (adherent) is attached to the surface layer of the release film and then peeled off from the surface layer to the object, the components contained in the surface layer of the release film are less likely to migrate to the surface of the object, and (2) it also exhibits the characteristic that there is a small difference in release force before and after heating to a high temperature, for example, around 90 to 160°C. Because the release film according to this embodiment has these characteristics, it can be suitably used in manufacturing processes for electronic components and electronic circuit boards, manufacturing processes for thermosetting resin members such as fiber-reinforced plastics, and in the medical field such as poultices and bandages. The release film according to this embodiment can be even more suitably used in each of the above fields if, in addition to the above characteristics, the release force at room temperature (the release force before heating to the high temperature mentioned above) is low and / or if the residual adhesion rate is excellent.

[0014] The release film according to this embodiment will be described in detail below. In this specification, the "~" in numerical ranges means greater than or equal to and less than or equal to. That is, the notation α~β means α or greater than or equal to β or greater than or equal to β or less, and the range includes α and β. Also, "(meth)acrylic" means "acrylic or methacrylic," and other similar terms have the same meaning.

[0015] The release film according to this embodiment is a laminated film having a base layer and a surface layer on at least one side of the base layer.

[0016] [Base material layer] As the base layer, in addition to layers containing resin (e.g., resin films), thin sheets such as paper, nonwoven fabric, and metal foil can be used. If the base layer is, for example, a layer containing resin, the resin may include polyester resins such as polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, polypropylene terephthalate, polypropylene naphthalate, polytrimethylene terephthalate, and polybutylene terephthalate; polyolefin resins such as polyethylene and polypropylene; polystyrene resins; acetylcellulose resins such as triacetylcellulose; acrylic resins such as polymethyl methacrylate; polyurethane resins; polycarbonate resins; polyamide resins; and polyvinyl chloride resins.

[0017] If the base layer is a resin-containing layer, it may contain only one type of resin, or it may contain a combination of two or more types. In the release film of this embodiment, the base layer is preferably a layer mainly containing at least one selected from the group consisting of polyester resins, polyolefin resins, and polystyrene resins, from the viewpoint of the processability of the surface layer, and more preferably a layer mainly containing at least one selected from the group consisting of polyester resins and polyolefin resins, from the viewpoint of adhesion to the surface layer (and adhesion to the other layer if another layer is interposed between the surface layer and the base layer).

[0018] Herein, in the present invention and this specification, the main component means a component that is present in an amount of 50% by mass or more, and the proportion of the main component is preferably 70% by mass or more, more preferably 80% by mass or more, even more preferably 90% by mass or more, and particularly preferably 95% by mass or more. The proportion of the main component may be 100% by mass.

[0019] The base layer, like the surface layer described later, may contain additives. The types and components of the additives are the same as those described in the section on the surface layer, and will not be explained here.

[0020] The base layer may be composed of an unoriented film, a uniaxially oriented film, or a biaxially oriented film. From the viewpoint of processability, transparency, and dimensional stability, the base layer is preferably composed of a biaxially oriented film.

[0021] The thickness of the base layer is preferably 15 μm or more, and more preferably 20 μm or more, from the viewpoint of processability. The thickness of the base layer is preferably 125 μm or less, and more preferably 50 μm or less, from the viewpoint of handling ease during product use. The thickness of the base layer is measured using a micrometer (JIS B-7502) in accordance with JIS C-2151, and specifically measured by the method described in the examples.

[0022] To improve the adhesion between the substrate layer and the surface layer described later, surface treatment may be applied to one or both sides of the substrate layer as desired. Examples of surface treatments include surface rippling treatments such as sandblasting or solvent treatment, corona discharge treatment, plasma treatment, chromic acid treatment, flame treatment, hot air treatment, or surface oxidation treatments such as ozone or ultraviolet irradiation treatment.

[0023] [Surface layer] The release film of this embodiment has a surface layer on a base layer. The surface layer is a layer that imparts release properties to the release film. The surface layer may be formed on the base layer via layers such as an adhesive layer between it and the base layer, but it is preferable that the surface layer is formed so that its main surface is in contact with the main surface of the base layer.

[0024] The main component forming the surface layer is a resin component. The resin component includes a modified acrylic resin (A) having an alkyl component and a crosslinkable functional group, a resin (B) different from the modified acrylic resin (A), and a crosslinking agent (D). In other words, the surface layer is composed of a cured product of a resin composition containing a modified acrylic resin (A) having an alkyl component and a crosslinkable functional group, a resin (B) different from the modified acrylic resin (A), and a crosslinking agent (D) as resin components. The modified acrylic resin (A), the resin (B) different from the modified acrylic resin (A), and the crosslinking agent (D) will be described in detail below.

[0025] <Modified acrylic resin (A)> Modified acrylic resin (A) having alkyl components and crosslinkable functional groups is a resin having alkyl groups as side chains relative to the main chain of acrylic resin. Modified acrylic resin (A) contains at least one constituent unit represented by the following general formula (I) (formed by monomer a described later). [ka]

[0026] In general formula (I), R 1 R represents a methyl group or a hydrogen atom. 2 This represents an alkyl group having 10 to 18 carbon atoms.

[0027] In general formula (I), alkyl group R 2 The number of carbon atoms is 10 to 18. When the number of carbon atoms is less than 9, it is generally difficult to achieve release properties in the modified acrylic resin (A). Also, when the number of carbon atoms exceeds 18, the peeling force becomes too high due to factors such as increased crystallinity, resulting in poor peeling performance as a release film. By having a long-chain alkyl group with 10 to 18 carbon atoms in the modified acrylic resin (A), the peeling performance becomes excellent. In addition, to improve the peeling performance, the R of general formula (I) 2 It is preferable that R is a linear alkyl group. 2 The number of carbon atoms is preferably 12 to 18, and more preferably 12 to 14. 2is a carbon number 12 to 1 A linear alkyl group with 8 carbon atoms is even more preferred, and a linear alkyl group with 12 to 14 carbon atoms is particularly preferred.

[0028] In the modified acrylic resin (A), examples of crosslinkable functional groups (reactive functional groups) include carboxyl groups, isocyano groups, epoxy groups, N-methylol groups, N-alkoxymethyl groups, hydroxyl groups, amino groups, thiol groups, hydrolyzable silyl groups, and the like. The number of crosslinkable functional groups may be one or two or more. Furthermore, the crosslinkable functional groups may be contained individually or in groups of two or more.

[0029] The modified acrylic resin (A) is a polymer obtained by polymerizing monomer a (an acrylic monomer having a carbon-carbon unsaturated double bond and an alkyl group having 10 to 18 carbon atoms in one molecule) which forms a structural unit represented by the general formula (I) above, as a monomer. The modified acrylic resin (A) may also be a copolymer obtained by copolymerizing monomer a with at least one monomer selected from the group consisting of monomer b (a monomer having a carbon-carbon unsaturated double bond and a crosslinkable functional group in one molecule), monomer c (an acrylic monomer having a carbon-carbon unsaturated double bond and an alkyl group having 1 to 9 or 19 or more carbon atoms in one molecule), and monomer d (a monomer different from monomers a, b, and c, which is copolymerizable with at least one of monomers a, b, and c). In particular, copolymers obtained by copolymerizing at least monomer a and monomer b are preferred as the modified acrylic resin (A).

[0030] [monomer a] Examples of monomer a include (meth)acrylic acid esters in which the ester portion is a long-chain alkyl group having 10 to 18 carbon atoms. Specifically, these include isodecyl (meth)acrylate, undecyl (meth)acrylate, dodecyl (meth)acrylate (also called lauryl (meth)acrylate), tridecyl (meth)acrylate, tetradecyl (meth)acrylate (also called myristyl (meth)acrylate), pentadecyl (meth)acrylate, hexadecyl (meth)acrylate (also called palmityl (meth)acrylate), stearyl (meth)acrylate, and the like.

[0031] The content ratio of constituent units derived from monomer a in the modified acrylic resin (A) is preferably about 50 to 99.99 parts by mass, more preferably about 70 to 99.9 parts by mass, even more preferably about 85 to 99.8 parts by mass, and even more preferably 85 to 99.5 parts by mass, with the total amount of constituent units contained in the modified acrylic resin (A) being 100 parts by mass, from the viewpoint of reducing the difference in peeling force before and after heating and further making it difficult for the components of the surface layer to transfer to the article. Monomer a may be of only one type, or two or more types may be mixed and used.

[0032] [monomer b] Monomer b is a monomer having a carbon-carbon unsaturated double bond and a crosslinkable functional group in one molecule. Because monomer b has a crosslinkable functional group, it can suitably bond with a resin (B) different from the modified acrylic resin (A) via the crosslinking agent (D) described later, thereby reducing the difference in peel strength of the release film before and after heating, and further suppressing the transfer of components of the surface layer to the article.

[0033] Examples of crosslinkable functional groups (reactive functional groups) include carboxyl groups, isocyano groups, epoxy groups, N-methylol groups, N-alkoxymethyl groups, hydroxyl groups, amino groups, thiol groups, and hydrolyzable silyl groups. Monomer b may be used alone or as a mixture of two or more types. Furthermore, monomer b may contain one crosslinkable functional group or two or more. In addition, the crosslinkable functional group may be contained alone or as two or more types.

[0034] Examples of monomer b containing a carboxyl group include acrylic acid, methacrylic acid, crotonic acid, itaconic acid, maleic acid, and styrene sulfonic acid. Other examples of monomer b containing a carboxyl group include N-(meth)acryloyl-p-aminobenzoic acid and N-(meth)acryloyl-5-aminosalicylic acid. Carboxyl group-containing (meth)acrylates can also be used as monomer b containing a carboxyl group. Examples of carboxyl group-containing (meth)acrylates include 1,4-di(meth)acryloxyethylpyromellitic acid, 4-(meth)acryloxyethyltrimellitic acid, and 2-(meth)acryloyloxybenzoic acid.

[0035] Examples of monomer b having an isocyanone group include (meth)acryloyloxyethyl isocyanate and (meth)acryloyloxypropyl isocyanate. Other examples include those obtained by reacting a hydroxy(meth)acrylate (e.g., 2-hydroxyethyl(meth)acrylate, 4-hydroxybutyl(meth)acrylate, etc.) with a polyisocyanate (e.g., toluene diisocyanate, isophorone diisocyanate, etc.).

[0036] Examples of monomer b having an epoxy group include glycidyl methacrylate, glycidyl cinnamate, glycidyl allyl ether, glycidyl vinyl ether, vinylcyclohexane monoepoxide, and 1,3-butadiene monoepoxide.

[0037] Examples of monomer b having an N-methylol group or an N-alkoxymethyl group include (meth)acrylamides having an N-monoalkoxymethyl group such as N-methylol(meth)acrylamide, N-methoxymethyl(meth)acrylamide, N-ethoxymethyl(meth)acrylamide, N-propoxymethyl(meth)acrylamide, and N-butoxymethyl(meth)acrylamide, as well as (meth)acrylamides having an N,N-dialkoxymethyl group such as N,N-dimethylol(meth)acrylamide, N,N-di(methoxymethyl)(meth)acrylamide, N,N-di(ethoxymethyl)(meth)acrylamide, N,N-di(propoxymethyl)(meth)acrylamide, and N,N-di(butoxymethyl)(meth)acrylamide.

[0038] Examples of monomer b containing a hydroxyl group include hydroxyl group-containing (meth)acrylates. Examples of hydroxyl group-containing (meth)acrylates include 2-hydroxyethyl (meth)acrylate, 1-hydroxypropyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, polyethylene glycol mono(meth)acrylate, polypropylene glycol mono(meth)acrylate, and polytetramethylene glycol mono(meth)acrylate. Other examples of monomer b containing a hydroxyl group include hydroxystyrene.

[0039] Examples of monomer b having an amino group include primary or secondary amino group-containing (meth)acrylates. Examples of primary or secondary amino group-containing (meth)acrylates include aminoethyl (meth)acrylate, ethylaminoethyl (meth)acrylate, aminopropyl (meth)acrylate, and ethylaminopropyl (meth)acrylate.

[0040] Examples of monomer b having a thiol group include thiol-containing (meth)acrylates. Examples of thiol-containing (meth)acrylates include 2-(methylthio)ethyl methacrylate.

[0041] Examples of monomer b having a hydrolyzable silyl group include (meth)acryloxyalkylalkoxysilanes such as γ-(meth)acryloxypropyltrimethoxysilane and γ-(meth)acryloxypropylmethyldimethoxysilane, (meth)acryloxyalkylalkoxyalkylsilanes, trimethoxyvinylsilane, dimethoxyethylsilane, triethoxyvinylsilane, triethoxyarylsilane, vinylmethyldimethoxysilane, vinylmethyldiethoxysilane, and vinyltris(2-methoxyethoxy)silane.

[0042] The monomer b is preferably at least one selected from the group consisting of 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 3-hydroxybutyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, polyethylene glycol mono(meth)acrylate, polypropylene glycol mono(meth)acrylate, polytetramethylene glycol mono(meth)acrylate, and hydroxystyrene, and more preferably at least one selected from the group consisting of 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 3-hydroxybutyl (meth)acrylate, and 4-hydroxybutyl (meth)acrylate.

[0043] When monomer b is at least one selected from the group consisting of 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 3-hydroxybutyl (meth)acrylate, and 4-hydroxybutyl (meth)acrylate, the modified acrylic resin (A) contains at least the constituent unit represented by the above general formula (I) and at least the constituent unit represented by the following general formula (II). [ka]

[0044] In general formula (II), R a R represents a methyl group or a hydrogen atom. b This represents -CH2CH2OH, -CH2-CHOH-CH3, -CH2CH2CH2OH, -CH2-CHOH-CH2CH3, -CH2CH2-CHOH-CH3, or -CH2CH2CH2CH2OH.

[0045] When the modified acrylic resin (A) contains constituent units derived from monomer b, the content ratio of constituent units derived from monomer b in the modified acrylic resin (A) is preferably about 0.01 to 20 parts by mass, more preferably about 0.1 to 10 parts by mass, even more preferably about 0.2 to 5 parts by mass, even more preferably about 0.5 to 3 parts by mass, and particularly preferably about 0.8 to 1.5 parts by mass, based on the total amount of constituent units contained in the modified acrylic resin (A) being 100 parts by mass, in order to reduce the difference in peeling force before and after heating and to make it difficult for the components of the surface layer to migrate to the article. When the modified acrylic resin (A) contains not only constituent units derived from monomer a but also constituent units derived from monomer b, its primary structure may be a random copolymer or a block copolymer.

[0046] [monomer c] Monomer c is an acrylic monomer having a carbon-carbon unsaturated double bond and an alkyl group having 1 to 9 or 19 or more carbon atoms in one molecule. Monomer c can be used, for example, to adjust the concentration of alkyl groups contained in the surface layer, thereby reducing the difference in peel strength of the release film before and after heating, and further contributing to suppressing the transfer of components of the surface layer to the article.

[0047] As monomer c, (meth)acrylic acid derivatives are preferred. As (meth)acrylic acid derivatives, monomers from which the constituent unit represented by the following general formula (III) can be derived are preferred. [ka]

[0048] In general formula (III), R 1 R represents a methyl group or a hydrogen atom. 3 This represents an alkyl group having 1 to 9 or 19 or more carbon atoms, and this alkyl group may be a modified alkyl group containing a fluorine atom, oxygen atom, nitrogen atom, sulfur atom, chlorine atom, bromine atom, silicon atom, etc.

[0049] Specific examples of monomer c include methyl (meth)acrylate, butyl (meth)acrylate, n-octyl (meth)acrylate, nonyl (meth)acrylate, stearyl (meth)acrylate, ethylhexyl (meth)acrylate, benzyl (meth)acrylate, (meth)acrylate salts, (meth)acrylonitrile, etc. Monomer c may be used alone or as a mixture of two or more types.

[0050] When the modified acrylic resin (A) contains constituent units derived from monomer c, the content ratio of constituent units derived from monomer c in the modified acrylic resin (A) is preferably about 0.01 to 20 parts by mass, and more preferably about 0.1 to 10 parts by mass, based on 100 parts by mass of the total constituent units contained in the modified acrylic resin (A), from the viewpoint of reducing the difference in peeling force before and after heating and further making it difficult for the components of the surface layer to transfer to the article.

[0051] [monomer d] Monomer d is a monomer different from monomers a, b, and c, and is a monomer that can copolymerize with at least one of monomers a, b, and c.

[0052] Specific examples of monomer d include (i') aromatic vinyl monomers, (ii') olefinic hydrocarbon monomers, (iii') vinyl ester monomers, (iv') vinyl halide monomers, and (v') vinyl ether monomers. Monomer d may be used alone or as a mixture of two or more types. Monomer d can be used, for example, to adjust the concentration of various functional groups contained in the surface layer, thereby reducing the difference in peel strength of the release film before and after heating, and further contributing to suppressing the transfer of components of the surface layer to the article.

[0053] Aromatic vinyl monomers include styrene, methylstyrene, ethylstyrene, chlorostyrene, and styrenes in which some hydrogen atoms are substituted with fluorine (e.g., monofluoromethylstyrene, difluoromethylstyrene, trifluoromethylstyrene, etc.).

[0054] Examples of olefinic hydrocarbon monomers include ethylene, propylene, butadiene, isobutylene, isoprene, and 1,4-pentadiene.

[0055] Examples of vinyl ester monomers include vinyl acetate.

[0056] Examples of vinyl halide monomers include vinyl chloride, vinylidene chloride, monofluoroethylene, difluoroethylene, and trifluoroethylene.

[0057] Examples of vinyl ether monomers include vinyl methyl ether.

[0058] When the modified acrylic resin (A) contains constituent units derived from monomer d, the content ratio of the constituent units derived from monomer d in the modified acrylic resin (A) is preferably about 0.01 to 20 parts by mass, and more preferably about 0.1 to 10 parts by mass, based on 100 parts by mass of the total constituent units contained in the modified acrylic resin (A), from the viewpoint of reducing the difference in peeling force before and after heating and further making it difficult for the components of the surface layer to transfer to the article.

[0059] From the viewpoint of reducing the difference in peeling force before and after heating, and furthermore making it difficult for components of the surface layer to transfer to the article, the weight-average molecular weight of the modified acrylic resin (A) is preferably 5 × 10 4 ~15×1 0 4 Therefore, far6×10 4 ~14×10 4 And more preferably 8 × 10 4 ~12×10 4 That is the case.

[0060] The content of modified acrylic resin (A) in the surface layer is not particularly limited, but from the viewpoint of reducing the difference in peeling force before and after heating, and further making it difficult for the components of the surface layer to transfer to the article, it is preferably 30 parts by mass or more, more preferably 40 parts by mass or more, even more preferably 50 parts by mass or more, even more preferably more than 50 parts by mass, and particularly preferably 55 parts by mass or more, based on the total of resin (A) and resin (B) constituting the surface layer being 100 parts by mass. Furthermore, the content of modified acrylic resin (A) in the surface layer is preferably 98 parts by mass or less, more preferably 90 parts by mass or less, even more preferably 80 parts by mass or less, particularly preferably 70 parts by mass or less, and especially preferably 60 parts by mass or less, based on the total of resin (A) and resin (B) constituting the surface layer being 100 parts by mass.

[0061] As a method for obtaining the modified acrylic resin (A), monomer a and, if necessary, monomers b, c, and d can be polymerized by known polymerization methods such as radical polymerization, anionic polymerization, and cationic polymerization.

[0062] An initiator may be used during polymerization. Azo compounds, organic peroxides, etc., can be used as initiators. Among these, azo compounds are preferred due to the ease of controlling polymerization yield and molecular weight, and azobisisobutyronitrile (AIBN) is more preferred. The amount of polymerization agent used is related to the yield. Due to the ease of controlling the molecular weight, the total amount of constituent units contained in the modified acrylic resin (A) is preferably 0.01 to 3 parts by mass, preferably 0.05 to 2 parts by mass, and more preferably 0.1 to 1.5 parts by mass, with 100 parts by mass being the total amount of constituent units.

[0063] Furthermore, the modified acrylic resin (A) may also be obtained by graft polymerization of alkyl groups onto a polymer obtained by polymerizing at least monomer b (a monomer having a carbon-carbon unsaturated double bond and a crosslinkable functional group). That is, a polymer having a structure in which alkyl groups are graft-polymerized onto some or all of the crosslinkable functional groups of the constituent units derived from monomer b (hereinafter referred to as modified acrylic resin (A')) can be used alone or in mixture with modified acrylic resin (A), similar to modified acrylic resin (A).

[0064] In the modified acrylic resin (A'), the number of carbon atoms in the graft-polymerized alkyl group is preferably about 10 to 18, more preferably about 12 to 14. The method for introducing the alkyl group by graft polymerization is not limited to known methods.

[0065] In the modified acrylic resin (A'), the same monomer b exemplified in the modified acrylic resin (A) can preferably be used. Details of monomer b are as described above.

[0066] The modified acrylic resin (A') may be a copolymer obtained by copolymerizing monomer b with at least one of monomer c and monomer d.

[0067] In the modified acrylic resin (A'), monomers c and d exemplified in the modified acrylic resin (A) can also be preferably used. Details of monomers c and d are as described above.

[0068] <Resin (B)> The resin component forming the surface layer includes a modified acrylic resin (A) along with a resin (B) that is different from the modified acrylic resin (A).

[0069] By incorporating the resin (B) in the surface layer, the difference in compatibility with the modified acrylic resin (A) can be utilized to facilitate segregation of the alkyl groups of the modified acrylic resin (A) onto the surface, reducing the difference in peel strength before and after heating, and further making it difficult for the components of the surface layer to transfer to the article.

[0070] The resin (B) is not particularly limited, but preferably at least one selected from the group consisting of polyester resins and acrylic resins. Furthermore, the polyester resin and acrylic resin can be appropriately selected from known polyester resins and acrylic resins. For example, as polyester resins, (i) non-convertible polyester resins obtained by a condensation reaction between a polyhydric alcohol and a polybasic acid, and modified with a condensate of a dibasic acid and a dihydric alcohol or a non-drying oil fatty acid, etc., and (ii) convertible polyester resins which are condensates of a dibasic acid and a trihydric or higher alcohol. In this embodiment, only one type of polyester resin (B) may be used, or two or more types may be mixed and used.

[0071] Polyhydric alcohols used as raw materials for polyester resins include, specifically, dihydric alcohols, trihydric alcohols, and polyhydric alcohols with tetrahydric or higher valencies. Examples of dihydric alcohols include ethylene glycol, diethylene glycol, triethylene glycol, propylene glycol, trimethylene glycol, tetramethylene glycol, and neopentyl glycol. Examples of trihydric alcohols include glycerin, trimethylolethane, and trimethylolpropane. Examples of polyhydric alcohols with tetrahydric or higher valencies include diglycerin, triglycerin, pentaerythritol, dipentaerythritol, mannitol, and sorbitol. These polyhydric alcohols may be used individually or in combination of two or more types.

[0072] Furthermore, specific examples of polybasic acids used as raw materials for polyester resins include aromatic polybasic acids, aliphatic saturated polybasic acids, aliphatic unsaturated polybasic acids, and polybasic acids obtained by the Diels-Alder reaction. Examples of aromatic polybasic acids include phthalic anhydride, terephthalic acid, isophthalic acid, and trimetic anhydride. Examples of aliphatic saturated polybasic acids include succinic acid, adipic acid, and sebacic acid. Examples of aliphatic unsaturated polybasic acids include maleic acid, maleic anhydride, fumaric acid, itaconic acid, and citraconic anhydride. Examples of polybasic acids obtained by the Diels-Alder reaction include cyclopentadiene-maleic anhydride adducts, terpene-maleic anhydride adducts, and rosin-maleic anhydride adducts. These polybasic acids may be used individually or in combination of two or more.

[0073] Examples of non-drying oil fatty acids used as denaturants include octylic acid, lauric acid, palmitic acid, stearic acid, oleic acid, linoleic acid, linolenic acid, eleostearic acid, ricinoleic acid, dehydrated ricinoleic acid, or coconut oil, linseed oil, tuna oil, castor oil, dehydrated castor oil, soybean oil, safflower oil, and their fatty acids. These may be used individually or in combination of two or more. Similarly, the polyester resin may be used individually or in combination of two or more.

[0074] Examples of acrylic resins include homopolymers of (meth)acrylic acid esters, copolymers of two or more different (meth)acrylic acid ester monomers, or copolymers of (meth)acrylic acid esters with other monomers. More specifically, examples of (meth)acrylic resins include (meth)acrylic acid esters such as polymethyl (meth)acrylate, polyethyl (meth)acrylate, polypropyl (meth)acrylate, polybutyl (meth)acrylate, (meth)acrylate-butyl (meth)acrylate copolymer, (meth)acrylate-butyl (meth)acrylate copolymer, ethylene-methyl (meth)acrylate copolymer, and styrene-methyl (meth)acrylate copolymer. Only one type of acrylic resin may be used, or two or more types may be mixed and used.

[0075] The resin (B), which is different from the modified acrylic resin (A), preferably has a reactive functional group in order to react with the crosslinking agent (D) described later. In particular, it is preferable that the reactive functional group is at least one selected from the group consisting of carboxyl groups and hydroxyl groups. If resin (B) has a hydroxyl group, the hydroxyl value of resin (B) is preferably 5 to 500 mg KOH / g, more preferably 10 to 300 mg KOH / g, and even more preferably 15 to 100 mg KOH / g.

[0076] The number-average molecular weight of resin (B) is preferably around 500 to 30,000, and more preferably around 1,000 to 20,000. When the number-average molecular weight of resin (B) is within the above range, the network structure when the surface layer is crosslinked with the crosslinking agent (D) tends to become denser, and segregation of the modified acrylic resin (A) having alkyl components and crosslinkable functional groups to the peel surface is more likely to occur.

[0077] While the content of resin (B) in the surface layer is not limited, from the viewpoint of reducing the difference in peeling force before and after heating, and further from the viewpoint of making it difficult for the components of the surface layer to transfer to the article, the total amount of resin (A) and resin (B) constituting the surface layer is preferably 2 parts by mass or more, more preferably 10 parts by mass or more, even more preferably 20 parts by mass or more, particularly preferably 30 parts by mass or more, and especially preferably 40 parts by mass or more, based on 100 parts by mass. Also, from the same viewpoint, the total amount of resin (A) and resin (B) constituting the surface layer is preferably 70 parts by mass or less, more preferably 60 parts by mass or less, even more preferably 50 parts by mass or less, even more preferably less than 50 parts by mass, and particularly preferably 45 parts by mass or less, based on 100 parts by mass.

[0078] <(D) Crosslinking agent> The resin component forming the surface layer contains a modified acrylic resin (A) and a resin (B), along with a crosslinking agent (D). The crosslinking agent (D) has the function of crosslinking modified acrylic resins (A) with each other, resins (B) with each other, or modified acrylic resins (A) and resins (B).

[0079] In this embodiment, the crosslinking agent (D) is a melamine compound. The melamine compound has a structure in which all hydrogen atoms of the amino group are substituted with at least one of an alkoxyalkyl group and an alkanol group. In other words, the melamine compound can be said to have at least one of the group consisting of alkoxyalkyl groups and alkanol groups as substituents on the amino group. Furthermore, the melamine compound has a structural unit in which three amino groups are bonded to a triazine ring, and in this embodiment, the total of six substituents bonded to the three amino groups are at least one of the group consisting of alkoxyalkyl groups and alkanol groups, and it can be said that there are no other substituents such as hydrogen atoms.

[0080] More specifically, melamine compounds can be represented by the following general formula (IV). [ka]

[0081] In general formula (IV), the six substituents R on the three amino groups bonded to the triazine ring are each groups in which a hydrogen atom of the amino group is substituted. Each of the six substituents R is independently either an alkoxyalkyl group or an alkanol group. Furthermore, n is a number greater than or equal to 1 and represents the average n-number of the melamine compound.

[0082] Alkoxyalkyl groups refer to C1-6 alkyloxy C1-6 alkyl groups, such as methoxymethyl group and 1-ethoxyethyl group. Alkanol groups refer to groups in which the hydrogen atom on the terminal methyl group of a linear or branched alkyl group is replaced by a hydroxyl group, such as hydroxymethyl group, 2-hydroxyethyl group, 3-hydroxypropyl group, 2-hydroxy-n-propyl group (-CH2-CHOH-CH3), and 2-hydroxy-1-methylethyl group. Here, C1-6 means the number of carbon atoms is between 1 and 6.

[0083] In this embodiment, from the viewpoint of reducing the difference in peeling force before and after heating, and furthermore, making it difficult for components of the surface layer to transfer to the article, in the melamine compound of general formula (IV), it is preferable that at least one of the six substituents R is an alkoxyalkyl group, more preferably three or more are alkoxyalkyl groups, and particularly preferable that all six are alkoxyalkyl groups. Also, in the general formula (IV), of the six substituents R, it is preferable that there are five or fewer alkanol groups, more preferably three or fewer, and even more preferably zero. In the examples described later, in the melamine compound of type F, all six substituents R are alkoxyalkyl groups.

[0084] In melamine compounds, the number of carbon atoms in the alkoxyalkyl group is preferably 2 to 5, and more preferably 2. Preferred specific examples of alkoxyalkyl groups include propoxymethyl, ethoxymethyl, and methoxymethyl groups, with the methoxymethyl group being particularly preferred among these. Furthermore, the number of carbon atoms in the alkanol group is preferably 1 to 3, and more preferably 1. Preferred specific examples of alkanol groups include propanol (3-hydroxypropyl), ethylol (2-hydroxyethyl), and methylol (hydroxymethyl) groups, with the methylol group being particularly preferred among these.

[0085] The average n-number of the melamine compound is preferably about 1.0 to 3.0, more preferably about 1.1 to 2.0, and even more preferably about 1.2 to 1.5. The crosslinking agent (D) may be of one type only, or two or more types may be mixed and used.

[0086] In this embodiment, from the viewpoint of reducing the difference in peeling force before and after heating, and furthermore, making it difficult for components of the surface layer to transfer to the article, the melamine compound is particularly preferably a compound represented by general formula (V). [ka] [Here, Me represents a methyl group.]

[0087] In general formula (V), the average n-quantity of the melamine compound is within the range described above.

[0088] In this embodiment, the resin component forming the surface layer may contain other crosslinking agents other than crosslinking agent (D), but it is preferable that the only crosslinking agent contained in the resin component is crosslinking agent (D).

[0089] Other crosslinking agents include, but are not limited to, polyfunctional amino compounds, isocyanate compounds (including monoisocyanates, diisocyanates, polyfunctional isocyanates, etc.), polyfunctional epoxy compounds, polyfunctional metal compounds, or dialdehydes, which are different from the melamine compounds mentioned above.

[0090] Examples of polyfunctional amino compounds different from the aforementioned melamine compounds include urea compounds, benzoguanamine compounds, and diamines. Examples of urea compounds include alkylated urea compounds (for example, Nikalac MX-270 manufactured by Nippon Carbide Industries, Ltd.). Examples of benzoguanamine compounds include benzoguanamine and methylated benzoguanamine. Examples of diamines include ethylenediamine, tetramethylenediamine, hexamethylenediamine, N,N'-diphenylethylenediamine, and p-xylylenediamine.

[0091] Examples of polyfunctional isocyanate compounds include diphenylmethane diisocyanate (MDI), tolylene diisocyanate (TDI), hexamethylene diisocyanate (HDI), isophorone diisocyanate (IPDI), trimethylhexamethylene diisocyanate (TMDI), xylene diisocyanate (XDI), naphthalene diisocyanate (NDI), trimethylolpropane (TMP) adduct TDI, TMP adduct HDI, TMP adduct IPDI, and TMP adduct XDI.

[0092] Examples of polyfunctional epoxy compounds include N,N,N',N'-tetraglycidylmetoxylendiamine and 1,3-bis(N,N-diglycidylaminomethyl)cyclohexane.

[0093] Examples of polyfunctional metal compounds include aluminum chelate compounds, titanium chelate compounds, and trimethoxyaluminum. Examples of aluminum chelate compounds include aluminum trisacetylacetonate and aluminum ethylacetoacetate diisopropylate. Examples of titanium chelate compounds include titanium tetraacetylacetonate, titanium acetylacetonate, titanium octylene glycolate, tetraisopropoxytitanium, and tetramethoxytitanium.

[0094] In the surface layer, the crosslinking agent (D) content is preferably 3 parts by mass or more, more preferably 4 parts by mass or more, and even more preferably 5 parts by mass or more, based on 100 parts by mass of the total of the modified acrylic resin (A) and the resin (B) different from the modified acrylic resin (A). From the viewpoint of reducing the difference in peeling force before and after heating and further making it difficult for the components of the surface layer to migrate to the article, the crosslinking agent (D) content is preferably 3 parts by mass or less, more preferably 20 parts by mass or less, and even more preferably 10 parts by mass or less, based on 100 parts by mass of the total of the modified acrylic resin (A) and the resin (B) different from the modified acrylic resin (A).

[0095] <Other ingredients> [Additives] The surface layer and the base layer may each contain, in addition to the main resin component, at least one additive as needed. Examples of additives include acid catalysts, antioxidants, stabilizers such as chlorine absorbers and ultraviolet absorbers, lubricants, plasticizers, flame retardants, antistatic agents, colorants, and antiblocking agents. Such additives may be added to the base layer and the surface layer within a range that does not impair the effects of the present invention. At least one additive may be contained in only one of the base layer and the surface layer, or in all layers of the base layer and the surface layer. Furthermore, the base layer and the surface layer may contain the same or different additives.

[0096] The "acid catalyst" improves the density of the coating film through a crosslinking reaction and suppresses the precipitation of oligomers. Suitable acid catalysts for this crosslinking reaction include, for example, p-toluenesulfonic acid, p-toluenesulfonate methyl, p-toluenesulfonate ethyl, p-toluenesulfonate n-butyl, benzenesulfonic acid, sulfonic acid, and methanesulfonic acid. One or more acid catalysts can be used in combination. The amount of acid catalyst used is preferably 0.1 parts by mass or more, more preferably 0.3 parts by mass or more, and even more preferably 0.5 parts by mass or more, per 100 parts by mass of the resin component constituting the surface layer. Furthermore, the amount of acid catalyst used is preferably 3 parts by mass or less, more preferably 2 parts by mass or less, and even more preferably 1.5 parts by mass or less, per 100 parts by mass of the resin component constituting the surface layer.

[0097] While not particularly limited, antioxidants include 2,6-di-tert-butyl-p-cresol (generic name: BHT), and phenolic, hindered amine, phosphite, lactone, and tocopherol-based antioxidants. Specifically, examples include dibutylhydroxytoluene, pentaerythritol tetrakis[3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate], 1,3,5-trimethyl-2,4,6-tris(3,5-di-t-butyl-4-hydroxy)benzene, and tris(2,4-di-t-butylphenyl)phosphite.

[0098] While not particularly limited, examples of "chlorine absorbents" include metal soaps such as calcium stearate.

[0099] While not particularly limited, examples of "ultraviolet absorbers" include benzotriazole (such as Tinuvin 328 from BASF), benzophenone (such as Cysorb UV-531 from Cytec), and hydroxybenzoate (such as UV-CHEK-AM-340 from Ferro).

[0100] The term "plasticizer" is not particularly limited, but examples include citrate esters, dibutyl phthalate, polyethylene glycols, propylene glycols, and glycerin.

[0101] The "flame retardant" is not particularly limited, but examples include halogen compounds, aluminum hydroxide, magnesium hydroxide, phosphates, borates, and antimony oxides.

[0102] The "antistatic agent" is not particularly limited, but examples include glycerol monoesters (such as glycerol monostearate) and ethoxylated secondary amines.

[0103] Examples of "coloring agents" include various colored dyes, colored pigments, and fluorescent dyes.

[0104] "Antiblocking agents" are added to prevent blocking and are not particularly limited as long as they do not exhibit the effect of a nucleating agent. Examples of antiblocking agents include inorganic pigments such as silica particles, alumina, (synthetic) zeolite, calcium carbonate, kaolin, talc, mica, zinc oxide, magnesium oxide, quartz, magnesium carbonate, barium sulfate, and titanium dioxide, as well as organic pigments such as polystyrene, polyacrylic particles, polymethyl methacrylate (PMMA) particles, crosslinked polyethylene particles, polyester, polyamide, polycarbonate, polyether, polyethersulfone, polyetherimide, polyphenylene sulfide, polyetheretherketone, polyamideimide, (crosslinked) melamine resin, benzoguanamine resin, urea resin, amino resin, furan resin, epoxy resin, phenol resin, unsaturated polyester resin, vinyl ester resin, diallyl phthalate resin, polyimide resin, fatty acid amide, and fatty acid glycerol ester compounds. The antiblocking agent is preferably a pigment having a particle size of 0.1 μm to 10 μm, and PMMA and silica particles are more preferred because they have excellent antiblocking properties and provide excellent slipperiness. For example, by incorporating such a pigment into the aforementioned substrate layer, the slipperiness of the front and back surfaces of the substrate layer is improved, and blocking can be suppressed.

[0105] Furthermore, in this embodiment, it is preferable that the surface layer substantially does not contain silicone compounds in order to avoid adverse effects on electrical components, etc. "Substantially containing silicone compounds" means that the amount of silicone compounds is preferably 500 μg / g or less, and more preferably 100 μg / g or less.

[0106] From the viewpoint of improving peelability, the thickness of the surface layer is preferably 0.01 μm or more, more preferably 0.05 μm or more, and particularly preferably 0.1 μm or more. From the viewpoint of migration of polymer components to the substrate layer, the thickness of the surface layer is preferably 3 μm or less, more preferably 1.5 μm or less, and more preferably 1 μm or less. The thickness of the surface layer is observed using a transmission electron microscope (TEM) (for example, the "HT7700" manufactured by Hitachi High-Technologies Corporation), and is specifically measured by the method described in the examples.

[0107] [Method for preparing the surface layer] The surface layer can be formed by laminating resin components that form the surface layer onto a substrate layer. A preferred embodiment of the method for producing the surface layer involves applying a coating solution containing a modified acrylic resin (A), a resin different from the modified acrylic resin (B) (B), a crosslinking agent (D), and other components as needed, along with at least one solvent, onto a substrate layer to crosslink the resin (A) and the resin (B), and then removing the solvent from the coating layer obtained by the coating process.

[0108] The solvent is not particularly limited as long as it can dissolve and / or uniformly disperse components other than the solvent in the coating solution. Examples of the solvent include ketone / ester-based organic solvents such as methyl ethyl ketone (MEK) and ethyl acetate, and organic solvents such as aliphatic hydrocarbons such as n-heptane and methylcyclohexane. The boiling point of the solvent is preferably 10 to 150°C, and more preferably 20 to 120°C, from the viewpoint of improving the handling of the coating solution and the manufacturing efficiency of the releaseable film. Only one type of solvent may be used, or two or more types may be mixed and used.

[0109] The concentration of components other than the solvent in the coating solution (i.e., the concentration of solid components remaining on the surface layer after the solvent has been removed, for example, the total concentration of a modified acrylic resin (A), a resin different from the modified acrylic resin (B), a crosslinking agent (D), and other components added as needed) is not limited, but from the viewpoint of the stability and coating suitability of the coating solution, it is preferably 1 to 24% by mass, more preferably 1 to 19% by mass, even more preferably 2 to 14% by mass, and particularly preferably 2 to 10% by mass, relative to the total amount of the coating solution. The coating method is not particularly limited and includes, for example, a blade coater, air knife coater, roll coater, bar coater, gravure coater, microgravure coater, rod blade coater, lip coater, die coater, curtain coater, or a method using a printing press.

[0110] A method for crosslinking resin (A) and resin (B) in the coating layer is to heat the coating layer in the presence of the crosslinking agent (D). For example, this could be done by applying hot air to the coating layer, or by heating the coating layer with electromagnetic waves such as infrared rays. The method for removing the solvent from the coating layer is not particularly limited as long as the solvent can be evaporated. Note that removing the solvent does not only mean completely removing it, but also includes removing it to the extent that a layer can be formed. Examples of methods for removing the solvent include drying the coating layer by blowing air on it, and drying the coating layer by heating it. From the viewpoint of achieving both solvent removal and promotion of the crosslinking reaction, the drying temperature by air or heating temperature is preferably 70 to 170°C, and more preferably 90 to 150°C. Furthermore, the drying time or heating time is preferably 10 to 300 seconds, more preferably 15 to 90 seconds, and even more preferably 20 to 50 seconds.

[0111] The release film of this embodiment may or may not be stretched, but from the viewpoint of easily obtaining good, light release properties, it is preferable that the surface layer is unstretched.

[0112] [Surface roughening of release film] In this embodiment, the surface of the release film may be given a fine surface roughness to improve winding suitability, to the extent that it does not interfere with lamination or other processes when used as a release film. Methods for giving the surface of the release film a fine surface include embossing, etching, and various known surface roughening methods.

[0113] The release film of this embodiment can be appropriately set according to the application, ranging from a very light (very low) T-peel release force to a moderately light (moderately low) T-peel release force. From the viewpoint of easily improving the adhesion of the release film to the adherend, it is preferably 0.01 N / 25 mm or more, more preferably 0.02 N / 25 mm or more, and even more preferably 0.05 N / 25 mm or more. From the viewpoint of easily improving release properties, the T-peel release force is preferably 2.00 N / 25 mm or less, more preferably 1.50 N / 25 mm or less, more preferably 1.00 N / 25 mm or less, more preferably 0.70 N / 25 mm or less, more preferably 0.50 N / 25 mm or less, more preferably 0.40 N / 25 mm or less, more preferably 0.30 N / 25 mm or less, more preferably 0.25 N / 25 mm or less, more preferably 0.22 N / 25 mm or less, and even more preferably 0.20 N / 25 mm or less. The T-shaped peel strength of a release film is measured by the following method.

[0114] [T-shaped peeling force] In a room temperature (25°C) environment, a 50mm wide x 200mm long polyester adhesive tape (Nitto Denko Corporation NO.31B tape, acrylic adhesive) is applied to the surface of the release film on the surface layer side by rolling a 2kg roller back and forth twice. The resulting film is heated at 160°C for 90 seconds, and then left to stand for 20 hours in an environment of 70°C and 50% humidity. Next, in a room temperature (25°C) environment, a 25mm wide sample is cut from the resulting film and used as the measurement sample. A tensile test machine (e.g., Minebea Inc. Technograph TGI-1kN universal tensile test machine) is used to perform a T-shaped peel at a speed of 1000mm / min, and the peeling force is measured. The value measured in this way is defined as the T-shaped peeling force (T-shaped peeling force before heating).

[0115] Furthermore, the T-shaped peeling force of the release film in this embodiment after heating is preferably small compared to the T-shaped peeling force before heating. The value of (T-shaped peeling force after heating) - (T-shaped peeling force before heating) is preferably -0.20 to +0.20, more preferably -0.10 to +0.10, even more preferably -0.08 to +0.05, and particularly preferably -0.04 to +0.02. The T-shaped peeling force of the release film after heating is measured by the following method.

[0116] [T-peel peeling force after heating] In a normal temperature (25°C) environment, a 50mm wide x 200mm long polyester adhesive tape (Nitto Denko Corporation NO.31B tape, acrylic adhesive) is applied to the surface of the release film by rolling a 2kg roller back and forth twice to obtain a sample with the tape applied before processing. Next, the sample with the tape applied is subjected to a heat treatment at 160°C for 90 seconds. A hot air dryer is used for this heat treatment. Here, the heat treatment at 160°C for 90 seconds means that the sample with the tape applied is placed in a hot air dryer set to 160°C. Next, a weight is placed on the sample with a load of 5kPa, and it is left to stand for 20 hours in an environment of 70°C and 50% humidity. Next, in a room temperature environment (25°C), a sample cut to a width of 25 mm from the obtained film is used as the measurement sample, and a T-shaped peel is performed at a speed of 1000 mm / min using a tensile testing machine (for example, a universal tensile testing machine, Technograph TGI-1kN, manufactured by Minebea Co., Ltd.), and the peeling force at that time is measured. The value measured in this way is defined as the T-shaped peeling force after heating.

[0117] [Thickness of the release film] The thickness of the release film is preferably 18 μm or more, and more preferably 20 μm or more, from the viewpoint of ease of handling as a release film. The thickness of the release film is preferably 100 μm or less, and more preferably 50 μm or less, from the viewpoint of ease of handling as a release film. The thickness of the release film in this embodiment is measured using a micrometer (JIS B-7502) in accordance with JIS C-2151.

[0118] The release film of this embodiment has good release properties and maintains these good release properties even after heat treatment, making it excellent as a release film. The release film of this embodiment can be widely used in industrial and medical fields, and is suitably used as, for example, a release film used in surface protection films and adhesive tapes, a release liner or separator film, a separator film for process tapes (dicing, die bonding, backgrinding) used in semiconductor product manufacturing, a carrier for forming unfired sheets in ceramic capacitor manufacturing, a carrier in composite material manufacturing, a separator film for protective materials, etc. The release film of this embodiment is used by being attached to substrates such as tapes or sheets; resin components of electrical equipment, electronic equipment, wearable devices, medical devices and building materials; intermediate components manufactured in the process of semiconductor product manufacturing; various electrical components (hard disks, motors, connectors, switches, etc.); the object to which it is used when used as a carrier; and dry film resists. Furthermore, if the adherend described above has an adhesive layer (for example, a solvent-based, emulsion-based, or hot-melt pressure-sensitive adhesive layer), the release film of this embodiment may be used by attaching it to the adherend such that the surface layer of the release film of this embodiment and the adhesive layer are bonded together. The method of attaching the release film of this embodiment to an object is not particularly limited. The release film of this embodiment may be attached to an object by, for example, cutting the release film appropriately according to the area to be attached, or, if both the release film of this embodiment and the object to which it is attached are wound in a roll, they may be bonded together roll to roll. [Examples]

[0119] The present invention will be described in detail below with reference to examples and comparative examples. However, the present invention is not limited to the examples. Unless otherwise specified, parts and % refer to "parts by mass" and "mass%", respectively.

[0120] [Measurement Method and Evaluation Method] The various measurement and evaluation methods used in the examples and comparative examples are as follows:

[0121] [Thickness of the surface layer] After cutting the sample, the sample surface was coated with Os and embedded in resin. Next, trimming, surface preparation, and ultrathin sectioning were performed using an ultramicrotome equipped with a diamond knife, followed by observation with a transmission electron microscope (TEM). Sectioning device: Ultramicrotome (LEICA EM UC7, manufactured by Leica Corporation) Knife; DIATOME ULTRADRY Observation equipment: TEM (HT7700 model, manufactured by Hitachi High-Technologies Corporation) Acceleration voltage: 100kV Photo magnification: ×300,000x

[0122] [Thickness of the base layer and release film] The thickness of the release film and substrate layer was measured using a micrometer (JIS B-7502) in accordance with JIS C-2151.

[0123] [T-shaped peeling force] A polyester adhesive tape measuring 50 mm in width and 200 mm in length (Nitto Denko Corporation NO.31B tape, acrylic adhesive) was applied to the surface of the release film by rolling a 2 kg roller back and forth twice, to obtain a pre-treatment product. Next, a weight was placed on the attached product to create a load of 5 kPa, and it was left undisturbed for 20 hours in an environment of 70°C and 50% humidity. Next, under room temperature conditions, samples were cut from each treated and attached sample to a width of 25 mm. These samples were used as measurement samples, and a T-shaped peel test was performed at a speed of 1000 mm / min using a peel tester (Technograph TGI-1kN, universal tensile testing machine, manufactured by Minebea Co., Ltd.), and the peel force was measured. Each measurement was performed three times, and the average value was taken as the T-shaped peel force (pre-heating T-shaped peel force) of each peelable film. The results are shown in Table 1.

[0124] [T-peel peeling force after heating] A polyester adhesive tape measuring 50 mm in width and 200 mm in length (Nitto Denko Corporation NO.31B tape, acrylic adhesive) was applied to the surface of the release film by rolling a 2 kg roller back and forth twice, to obtain a pre-treatment product. Next, the attached product was subjected to a heat treatment at 160°C for 90 seconds. A hot air dryer was used for this heat treatment. Here, the heat treatment at 160°C for 90 seconds means that the attached product was placed in a hot air dryer set to 160°C. Next, a weight was placed on the attached product to apply a load of 5 kPa, and it was left standing for 20 hours in an environment of 70°C and 50% humidity. Then, the T-peel peel force after heating was obtained using the same method as the measurement and calculation method for the T-peel peel force described in [T-peel peel force] above. The results are shown in Table 1.

[0125] [Evaluation of residual adhesion rate] In the aforementioned [T-shaped peel force] test, the polyester adhesive tape used when measuring the T-shaped peel force on the surface layer side of each peelable film (the polyester adhesive tape after being peeled off during the measurement) was attached to a stainless steel plate (SUS plate) by moving a 2 kg roller back and forth twice. Next, a T-shaped peel test was performed on the attached product having the stainless steel plate obtained as described above, at a speed of 1000 mm / min, and the peel force (X) at that time was measured. On the other hand, in the aforementioned [T-shaped peel force] test, a T-shaped peel test was performed in the same manner as above, except that polyester adhesive tape was attached to the surface of a Teflon sheet (Skibbed Tape MSF-100, 100 μm thick, manufactured by Chuko Chemical Industries, Ltd.) instead of the film surface on the surface layer side of the peelable film. Furthermore, the polyester adhesive tape that had been peeled off in the peel test was attached to a stainless steel plate (SUS plate) by moving a 2 kg roller back and forth twice. Next, a T-shaped peel test was performed on the attached product having the stainless steel plate obtained as described above, at a speed of 1000 mm / min, and the peel force (Y) at that time was measured. Next, the residual adhesion rate was determined using the following formula. A lower residual adhesion rate indicates that the components of the surface layer of the release film are more likely to transfer to the polyester adhesive tape. A residual adhesion rate of 100% means that the components of the surface layer of the release film have not transferred to the polyester adhesive tape to the same extent as the components of the surface of the Teflon sheet have not transferred to the polyester adhesive tape, making this the most preferable release film according to this embodiment. The results are shown in Table 1. Residual adhesion rate (%)=(X) / (Y)×100

[0126] In the release film according to this embodiment, the residual adhesion rate is preferably 84% or higher, more preferably 87% or higher, even more preferably 90% or higher, even more preferably 93% or higher, and particularly preferably 97% or higher. The residual adhesion rate may be 100%.

[0127] <Example 1> In a 1-liter flask equipped with a stirrer, nitrogen inlet tube, thermometer, and condenser, 99 parts by mass of lauryl acrylate (LA) as monomer a, 1 part by mass of 2-hydroxyethyl acrylate (HEA) as monomer b, 0.2 parts by mass of azobisisobutyronitrile (AIBN) as a polymerization initiator, 100 parts by mass of toluene, and 100 parts by mass of ethyl acetate were added. Next, the polymerization reaction was carried out in the flask under a nitrogen stream at 80°C for 2 hours, and then 1.0 part by mass of azobisisobutyronitrile was added and polymerization was carried out for another 2 hours to obtain a solution containing alkyl acrylate-HEA copolymer (hereinafter referred to as "modified acrylic resin (A)") (solid content 30% by mass). The weight-average molecular weight of the obtained modified acrylic resin (A) was 10.5 × 10⁻⁶. 4 That was the case. Furthermore, the polyester resin α, which is resin (B), is Byron M802 (manufactured by Toyobo Co., Ltd., number average molecular weight (Mn): 3 × 10⁻¹⁰ 3The following were prepared: a hydroxyl value of 37 mg KOH / g and a solid content of 70% by mass; Nikalac MW-30MLF (manufactured by Nippon Carbide Industries, Ltd., average 1.3-mer, 98% by mass) as the melamine crosslinking agent (D) (Type F described later) represented by the general formula (V) above; and Dryer 900 (manufactured by Hitachi Chemical Co., Ltd., p-toluenesulfonic acid, 50% by mass) as the acid catalyst (E). Next, a solution containing modified acrylic resin (A), a resin (B) different from modified acrylic resin (A), and a melamine crosslinking agent (D) were mixed and stirred in a mixed solvent of toluene:methyl ethyl ketone (MEK) = 30:70 (mass ratio). Then, an acid catalyst (E) was added and stirred. At this point, the modified acrylic resin (A) solution, resin (B), melamine crosslinking agent (D), and acid catalyst (E) were mixed and stirred so that, on a solid content basis, the amounts were 56 parts by mass of the modified acrylic resin (A), 44 parts by mass of the polyester resin, 6 parts by mass of the melamine crosslinking agent, and 0.7 parts by mass of the acid catalyst (E). This yielded coating solution 1 with a solid content concentration of 4.4% by mass and an acid catalyst concentration of 0.03% by mass. Next, a 38 μm thick biaxially oriented polyethylene terephthalate film (biaxially oriented PET film, "E5100" manufactured by Toyobo Co., Ltd.) was prepared as the base layer. Next, the coating liquid 1 was applied onto the substrate layer using a Meyer bar (manufactured by Yasuda Seiki Seisakusho Co., Ltd., shaft diameter: 6.35 mmφ, ROD No. 4), and dried in an explosion-proof dryer at 140°C for 30 seconds. This yielded the release film of Example 1 having a substrate layer and a surface layer (surface layer thickness: 0.2 μm).

[0128] <Example 2> The modified acrylic resin (A)-containing solution, resin (B), melamine crosslinking agent (D), and acid catalyst (E) were mixed and stirred in such a manner that the solid content was 56 parts by mass of the modified acrylic resin (A), 44 parts by mass of the polyester resin, 6 parts by mass of the melamine crosslinking agent, and 1.1 parts by mass of the acid catalyst (E), respectively, to obtain coating solution 2 (solid content concentration 2.8% by mass, acid catalyst concentration 0.03% by mass). The coating solution 2 was then coated onto a substrate layer to a thickness of 0.1 μm after drying. The other operations were carried out in the same manner as in Example 1 to obtain the release film of Example 2.

[0129] <Example 3> The modified acrylic resin (A)-containing solution, resin (B), melamine crosslinking agent (D), and acid catalyst (E) were mixed and stirred in such a ratio of 75 parts by mass of the modified acrylic resin (A), 25 parts by mass of the polyester resin, 6 parts by mass of the melamine crosslinking agent, and 0.7 parts by mass of the acid catalyst (E) on a solid content basis to obtain coating solution 3 (solid content concentration 4.4% by mass, acid catalyst concentration 0.03% by mass). The other operations were carried out in the same manner as in Example 1 to obtain the release film of Example 3.

[0130] <Example 4> The modified acrylic resin (A)-containing solution, resin (B), melamine crosslinking agent (D), and acid catalyst (E) were mixed and stirred in such a way that the solid content was 95 parts by mass of the modified acrylic resin (A), 5 parts by mass of the polyester resin, 6 parts by mass of the melamine crosslinking agent, and 0.7 parts by mass of the acid catalyst (E), respectively, to obtain coating solution 4 (solid content concentration 4.4% by mass, acid catalyst concentration 0.03% by mass). The other operations were carried out in the same manner as in Example 1 to obtain the release film of Example 4.

[0131] <Example 5> The modified acrylic resin (A)-containing solution, resin (B), melamine crosslinking agent (D), and acid catalyst (E) were mixed and stirred in such a way that the solid content was 32 parts by mass of the modified acrylic resin (A), 68 parts by mass of the polyester resin, 6 parts by mass of the melamine crosslinking agent, and 0.7 parts by mass of the acid catalyst (E), respectively, to obtain coating solution 5 (solid content concentration 4.4% by mass, acid catalyst concentration 0.03% by mass). The other operations were carried out in the same manner as in Example 1 to obtain the release film of Example 5.

[0132] <Example 6> The weight-average molecular weight of the modified acrylic resin (A) is 8.1 × 10 4 To achieve this result, the amount of azobisisobutyronitrile (AIBN) used and the temperature during the polymerization reaction were changed. The other operations were the same as in Example 1 to obtain the release film of Example 6.

[0133] <Example 7> The weight-average molecular weight of the modified acrylic resin (A) is 5.8 × 10 4 To achieve this result, the amount of azobisisobutyronitrile (AIBN) used and the temperature during the polymerization reaction were changed. The other operations were the same as in Example 1 to obtain the release film of Example 7.

[0134] <Example 8> The weight-average molecular weight of the modified acrylic resin (A) is 13.0 × 10 4 To achieve this result, the amount of azobisisobutyronitrile (AIBN) used and the temperature during the polymerization reaction were changed. The other operations were the same as in Example 1 to obtain the release film of Example 8.

[0135] <Example 9> In a 1-liter flask equipped with a stirrer, nitrogen inlet tube, thermometer, and condenser, 99.5 parts by mass of lauryl acrylate (LA) as monomer a, 0.5 parts by mass of 2-hydroxyethyl acrylate (HEA) as monomer b, 0.2 parts by mass of azobisisobutyronitrile (AIBN) as an initiator, 100 parts by mass of toluene, and 100 parts by mass of ethyl acetate were added. Next, a polymerization reaction was carried out in the flask under a nitrogen stream at 80°C for 2 hours, and then 1.0 part by mass of azobisisobutyronitrile was added and polymerization was carried out for another 2 hours to obtain a modified acrylic resin (A) containing solution (solid content 30% by mass). The weight-average molecular weight of the obtained modified acrylic resin (A) was 6.8 × 10⁶. 4 The result was obtained by performing the same operations as in Example 1 for the other operations, thereby obtaining the release film of Example 9.

[0136] <Example 10> In a 1-liter flask equipped with a stirrer, nitrogen inlet tube, thermometer, and condenser, 98.0 parts by mass of lauryl acrylate (LA) as monomer a, 2.0 parts by mass of 2-hydroxyethyl acrylate (HEA) as monomer b, 0.2 parts by mass of azobisisobutyronitrile (AIBN) as an initiator, 100 parts by mass of toluene, and 100 parts by mass of ethyl acetate were added. Next, a polymerization reaction was carried out in the flask under a nitrogen stream at 80°C for 2 hours, and then 1.0 part by mass of azobisisobutyronitrile was added and polymerization was carried out for another 2 hours to obtain a modified acrylic resin (A) containing solution (solid content 30% by mass). The weight-average molecular weight of the obtained modified acrylic resin (A) was 10.3 × 10⁶. 4 The other operations were performed in the same manner as in Example 1 to obtain the peelable film of Example 10.

[0137] <Example 11> In a 1-liter flask equipped with a stirrer, nitrogen inlet tube, thermometer, and condenser, 99.0 parts by mass of isodecyl acrylate (IDAA) as monomer a, 1.0 part by mass of 2-hydroxyethyl acrylate (HEA) as monomer b, 0.2 parts by mass of azobisisobutyronitrile (AIBN) as an initiator, 100 parts by mass of toluene, and 100 parts by mass of ethyl acetate were added. Next, a polymerization reaction was carried out in the flask under a nitrogen stream at 80°C for 2 hours, and then 1.0 part by mass of azobisisobutyronitrile was added and polymerization was carried out for another 2 hours to obtain a modified acrylic resin (A) containing solution (solid content 30% by mass). The weight-average molecular weight of the obtained modified acrylic resin (A) was 10.9 × 10⁶. 4 The same procedure as in Example 1 was followed to obtain the peelable film of Example 11.

[0138] <Example 12> In a 1-liter flask equipped with a stirrer, nitrogen inlet tube, thermometer, and condenser, 99.0 parts by mass of stearyl acrylate (STA) as monomer a, 1.0 part by mass of 2-hydroxyethyl acrylate (HEA) as monomer b, 0.2 parts by mass of azobisisobutyronitrile (AIBN) as an initiator, 100 parts by mass of toluene, and 100 parts by mass of ethyl acetate were added. Next, a polymerization reaction was carried out in the flask under a nitrogen stream at 80°C for 2 hours, and then 1.0 part by mass of azobisisobutyronitrile was added and polymerization was carried out for another 2 hours to obtain a modified acrylic resin (A) containing solution (solid content 30% by mass). The weight-average molecular weight of the obtained modified acrylic resin (A) was 7.3 × 10⁻⁶. 4 The result was obtained by performing the same operations as in Example 1 for the other steps.

[0139] <Example 13> The release film of Example 13 was obtained in the same manner as in Example 1, except that an acrylic resin (Acrydic WMG-521, manufactured by DIC Corporation, Tg=30℃, acid value: 6.5 mg KOH / g, solid content 60% by mass) was used as resin (B) instead of polyester resin.

[0140] <Example 14> As the polyester resin (B), instead of polyester resin α (Byron M802), polyester resin β (Byron 20SS (manufactured by Toyobo Co., Ltd., number average molecular weight (Mn): 17 × 10) can be used. 3 A peelable film of Example 14 was obtained in the same manner as in Example 1, except that a hydroxyl value of 6 mg KOH / g and a solid content of 30% by mass were used.

[0141] <Example 15> In a 1-liter flask equipped with a stirrer, nitrogen inlet tube, thermometer, and condenser, 99 parts by mass of lauryl acrylate (LA) as monomer a, 1 part by mass of 2-hydroxyethyl acrylate (HEA) as monomer b, 0.2 parts by mass of azobisisobutyronitrile (AIBN) as an initiator, 100 parts by mass of toluene, and 100 parts by mass of ethyl acetate were added. Next, a polymerization reaction was carried out in the flask under a nitrogen stream at 80°C for 2 hours, and then 1.0 part by mass of azobisisobutyronitrile was added and polymerization was carried out for another 2 hours to obtain a modified acrylic resin (A) containing solution (solid content 30% by mass). The weight-average molecular weight of the obtained modified acrylic resin (A) was 10.5 × 10⁶. 4 That was the case. Furthermore, a different resin (B) from the modified acrylic resin (A) is used: polyester resin α (Byron M802 (manufactured by Toyobo Co., Ltd., number average molecular weight (Mn): 3 × 10) 3 The following were prepared: (hydroxyl value: 37 mg KOH / g, solids content 70% by mass), as a melamine crosslinking agent (D), Nikalac MS-11 (manufactured by Nippon Carbide Industries, Ltd., average 1.8-mer, 60% by mass), which is type M (a melamine compound in which all substituents R of the three amino groups bonded per constituent unit are either methoxymethyl groups or methylol groups, and at least one of the substituents R is a methylol group), and as an acid catalyst (E), Dryer 900 (manufactured by Hitachi Chemical Co., Ltd., p-toluenesulfonic acid 50% by mass). Next, a solution containing modified acrylic resin (A), a resin different from modified acrylic resin (A) (B), and a melamine crosslinking agent (D) were mixed and stirred in a mixed solvent of toluene:methyl ethyl ketone (MEK) = 30:70 (mass ratio), and then an acid catalyst (E) was added and stirred. At this point, the modified acrylic resin (A) solution, the resin different from modified acrylic resin (A) (B), the melamine crosslinking agent (D), and the acid catalyst (E) were mixed and stirred so that, on a solid content basis, the amounts were 56 parts by mass of the modified acrylic resin (A), 44 parts by mass of the polyester resin, 6 parts by mass of the melamine crosslinking agent, and 1.2 parts by mass of the acid catalyst (E). This yielded a coating solution 6 with a solid content concentration of 2.8% by mass and an acid catalyst concentration of 0.05% by mass. Next, a 38 μm thick biaxially oriented polyethylene terephthalate film (biaxially oriented PET film, "E5100" manufactured by Toyobo Co., Ltd.) was prepared as the base layer. Next, the coating liquid 6 was applied onto the substrate layer using a Meyer bar (manufactured by Yasuda Seiki Seisakusho Co., Ltd., shaft diameter: 6.35 mmφ, ROD No. 4), and dried in an explosion-proof dryer at 150°C for 60 seconds. This yielded the release film of Example 15 having a substrate layer and a surface layer (surface layer thickness: 0.1 μm).

[0142] <Comparative Example 1> As the melamine crosslinking agent (D), Nikalac MX-750 (manufactured by Nippon Carbide Industries, Ltd., average 2.2-mer, 80% by mass), a type IM melamine compound described later (where all substituents R of the three amino groups bonded per constituent unit are either methoxymethyl groups, methylol groups, or hydrogen atoms, and at least one of the substituents R is a methylol group, and at least one of the substituents R is a hydrogen atom), was used. The release film of Comparative Example 1 was obtained by performing the same operations as in Example 1 for the remaining steps.

[0143] <Comparative Example 2> As the melamine crosslinking agent (D), Nikalac MS-001 (manufactured by Nippon Carbide Industries, Ltd., average 5.7-mer, 60% by mass), which is of type IM as described later, was used. The same procedure as in Example 1 was followed to obtain the release film of Comparative Example 2.

[0144] <Comparative Example 3> Nikalac MX-750 was used instead of the melamine crosslinking agent (D). The same procedure as in Example 15 was followed to obtain the release film of Comparative Example 4.

[0145] <Comparative Example 4> Nikalac MS-001 was used instead of the melamine crosslinking agent (D). The same procedure as in Example 15 was followed to obtain the release film of Comparative Example 5.

[0146] <Comparative Example 5> The modified acrylic resin (A)-containing solution, a resin (B) different from the modified acrylic resin (A), a melamine crosslinking agent (D), and an acid catalyst (E) were mixed and stirred in such a ratio of 32 parts by mass of the modified acrylic resin (A), 68 parts by mass of the polyester resin, 6 parts by mass of the melamine crosslinking agent, and 0.7 parts by mass of the acid catalyst (E) on a solid content basis to obtain coating solution 7 (solid content concentration 4.4% by mass, acid catalyst concentration 0.03% by mass). The other operations were carried out in the same manner as in Example 15 to obtain the release film of Comparative Example 5.

[0147] [Table 1]

[0148] In Table 1, the meaning of the symbols for modified acrylic resin (A) is as follows: LA: Lauryl acrylate HEA: 2-hydroxyethyl acrylate IDAA: Isodecyl acrylate STA: Stearyl acrylate

[0149] In Table 1, the amino group substitution types for the melamine compound used as crosslinking agent D are as follows. The term "amino group substituent" below refers to a group in which a hydrogen atom of the amino group is substituted, and refers to R in formula (IV) above. The group R is a group that directly bonds to the nitrogen atom of the amino group. · Type F A melamine compound (represented by general formula (V)) in which all of the substituent Rs of the three amino groups bonded to each constituent unit (a total of six substituent Rs for the three amino groups) are methoxymethyl groups. · Type M A melamine compound in which all of the substituents R of the three amino groups bonded to each constituent unit are either methoxymethyl groups or methylol groups, and one or more of the substituents R are methylol groups. · Type IM A melamine compound in which all of the substituents R of the three amino groups bonded to each constituent unit are either a methoxymethyl group, a methylol group, or a hydrogen atom, and one or more of the substituents R are methylol groups, and one or more of the substituents R are hydrogen atoms.

Claims

1. A release film having a surface layer on a base layer, The main component forming the surface layer is a resin component. The resin component comprises a modified acrylic resin (A) having an alkyl component and a crosslinkable functional group, a resin (B) different from the modified acrylic resin (A), and a crosslinking agent (D). The modified acrylic resin (A) comprises at least the following general formula (I): 【Chemistry 1】 (In the above general formula (I), R 1 R represents a methyl group or a hydrogen atom. 2 (This represents an alkyl group having 10 to 18 carbon atoms.) It includes constituent units represented by, With the total amount of constituent units contained in the modified acrylic resin (A) being 100 parts by mass, the content ratio of the constituent units of the general formula (I) is 50 to 99.99 parts by mass. The content of the resin (B) in the surface layer is 30 parts by mass or more and 70 parts by mass or less, with the total amount of the modified acrylic resin (A) and the resin (B) constituting the surface layer being 100 parts by mass. The aforementioned resin (B) is an acrylic resin, The resin (B) has a hydroxyl group, The hydroxyl value of the aforementioned resin (B) is 5 to 500 mg KOH / g. The surface layer is composed of a cured product of a resin composition containing the resin component, The resin composition has an acid catalyst concentration of 0.03% by mass or more and 0.05% by mass or less, and a solid content concentration of 2.8% by mass or more and 4.4% by mass or less. The crosslinking agent (D) is a melamine compound having a structure in which all hydrogen atoms of the amino group are replaced by at least one of an alkoxyalkyl group and an alkanol group. The melamine compound is given by the following general formula (IV): 【Chemistry 2】 [In general formula (IV), all substituents R are alkoxyalkyl groups, and n is a number of 1 or more.] A release film represented by [this symbol].

2. The modified acrylic resin (A) is defined by the following general formula (II): 【Transformation 3】 [In the aforementioned general formula (II), R a represents a methyl group or a hydrogen atom, and R b is -CH 2 CH 2 OH, -CH 2 -CHOH-CH 3 , -CH 2 CH 2 CH 2 OH, -CH 2 -CHOH-CH 2 CH 3 , -CH 2 CH 2 -CHOH-CH 3 , or -CH 2 CH 2 CH 2 CH 2 OH.] The release film according to claim 1, comprising a constituent unit represented by the above.

3. The weight-average molecular weight of the modified acrylic resin (A) is 5 × 10 4 ~15 x 10 4 The release film according to claim 1 or 2.

4. The release film according to any one of claims 1 to 3, wherein the content of the resin (B) in the surface layer is 40 parts by mass or more, with the total of the modified acrylic resin (A) and the resin (B) constituting the surface layer being 100 parts by mass.

5. The release film according to any one of claims 1 to 4, wherein the content of the resin (B) in the surface layer is less than 50 parts by mass, with the total of the modified acrylic resin (A) and the resin (B) constituting the surface layer being 100 parts by mass.

6. The release film according to any one of claims 1 to 5, wherein the alkoxyalkyl group has 2 to 5 carbon atoms, and the alkanol group has 1 to 3 carbon atoms.

7. A method for manufacturing a release film having a surface layer on a base layer, The process includes forming the surface layer on the substrate layer, The main component forming the surface layer is a resin component. The resin component comprises a modified acrylic resin (A) having an alkyl component and a crosslinkable functional group, a resin (B) different from the modified acrylic resin (A), and a crosslinking agent (D). The modified acrylic resin (A) comprises at least the following general formula (I): 【Chemistry 4】 (In the above general formula (I), R 1 R represents a methyl group or a hydrogen atom. 2 (This represents an alkyl group having 10 to 18 carbon atoms.) It includes constituent units represented by, With the total amount of constituent units contained in the modified acrylic resin (A) being 100 parts by mass, the content ratio of the constituent units of the general formula (I) is 50 to 99.99 parts by mass. The content of the resin (B) in the surface layer is 30 parts by mass or more and 70 parts by mass or less, with the total amount of the modified acrylic resin (A) and the resin (B) constituting the surface layer being 100 parts by mass. The aforementioned resin (B) is an acrylic resin, The resin (B) has a hydroxyl group, The hydroxyl value of the aforementioned resin (B) is 5 to 500 mg KOH / g. The surface layer is composed of a cured product of a resin composition containing the resin component, The resin composition has an acid catalyst concentration of 0.03% by mass or more and 0.05% by mass or less. The crosslinking agent (D) is a melamine compound having a structure in which all hydrogen atoms of the amino group are replaced by at least one of an alkoxyalkyl group and an alkanol group. The melamine compound is given by the following general formula (IV): 【Transformation 5】 [In general formula (IV), all substituents R are alkoxyalkyl groups, and n is a number of 1 or more.] A method for manufacturing a release film, represented by [the formula shown].

8. The method for producing a release film according to claim 7, wherein the resin composition has a solid content concentration of 2.8% by mass or more and 4.4% by mass or less.

Citation Information

Patent Citations

  • Release film manufacturing method and release film

    JP2015030795A

  • Laminated polyester film

    JP2017080969A

  • Thermal curing release coating agent, release film and manufacturing method therefor

    JP2018115224A

  • Releasable film

    JP2023093485A